A defence of true Protestants, abused for the service of popery, under the name of Presbyterians. In a dialogue between A. and L. two sons of the Church. Where it is debated, whether discenting Presbyterians be as bad or worse than papists; and other popish assertions are detected. [electronic resource] : (1680)
Summary goes here